1997
DOI: 10.1038/sj.onc.1200820
|View full text |Cite
|
Sign up to set email alerts
|

Expression of antisense RNA to S100A4 gene encoding an S100-related calcium-binding protein suppresses metastatic potential of high-metastatic Lewis lung carcinoma cells

Abstract: S100A4 (also known as pEL98/mts1/p9Ka/18A2/42A/ calvasculin/FSP1/CAPL), a member of S100-related calcium-binding proteins, has been implicated to play a role in metastasis. In the present study, we examined the e ect of antisense S100A4 RNA on metastatic potential of Lewis lung carcinoma (LLC) cells. High-metastatic A11 cells were transfected with the expression vector containing S100A4 cDNA in an inverted (antisense) orientation under the transcriptional control of the mouse metallothionein promoter. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 17 publications
7
92
0
Order By: Relevance
“…Conversely, the expression of antisense S100A4 mRNA in S100A4-expressing Lewis lung carcinoma cells lowered cell motility (Takenaga et al, 1997a). These results collectively support the assumption that S100A4 participates in regulating cell motility.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Conversely, the expression of antisense S100A4 mRNA in S100A4-expressing Lewis lung carcinoma cells lowered cell motility (Takenaga et al, 1997a). These results collectively support the assumption that S100A4 participates in regulating cell motility.…”
Section: Discussionsupporting
confidence: 79%
“…Cell motility was assessed by phagokinetic track assay as described elsewhere (Takenaga et al, 1994a(Takenaga et al, , 1997a. Cells were incubated for 24 h in growth medium containing 300 IU ml -1 IFN-γ, washed, and then seeded onto coverslips coated with 10 µg ml -1 BSA and colloidal gold particle.…”
Section: Cell Motility Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of Ca 2 þ -binding proteins are thought to be implicated in establishing the malignant and metastatic phenotypes of various tumours (Chen et al, 1997;Takenaga et al, 1997;Van Ginkel et al, 1998), and recent studies have reported altered expression of several Ca 2 þ -binding protein genes in a wide range of human malignancies (Bustin et al, 2001;Pietas et al, 2002;Lakshmikuttyamma et al, 2004;Imazawa et al, 2005). Regarding oral squamous cell carcinomas (OSCCs), aberrant expression of S100 Ca 2 þ -binding protein families seen in tumour sites has been correlated with cancer cell invasion or metastasis (Moriyama-Kita et al, 2004;Tsai et al, 2005).…”
mentioning
confidence: 99%
“…The S100A4 gene was originally isolated as a gene differentially expressed in highly metastatic mouse mammary adenocarcinoma cells (Ebralidze et al, 1989). Introduction of the S100A4 gene into nonmetastatic tumor cell lines and suppression of its activity in metastatic ones proved its involvement in metastasis formation Maelandsmo et al, 1996;Takenaga et al, 1997;Lloyd et al, 1998;Uozumi et al, 2000). Stimulation of tumor metastasis was demonstrated in two transgenic mouse models with overexpression of the S100A4 gene Davies et al, 1996).…”
Section: Introductionmentioning
confidence: 99%